2022
DOI: 10.1038/s42003-022-03530-6
|View full text |Cite
|
Sign up to set email alerts
|

Placental sex-dependent spermine synthesis regulates trophoblast gene expression through acetyl-coA metabolism and histone acetylation

Abstract: Placental function and dysfunction differ by sex but the mechanisms are unknown. Here we show that sex differences in polyamine metabolism are associated with escape from X chromosome inactivation of the gene encoding spermine synthase (SMS). Female placental trophoblasts demonstrate biallelic SMS expression, associated with increased SMS mRNA and enzyme activity. Polyamine depletion in primary trophoblasts reduced glycolysis and oxidative phosphorylation resulting in decreased acetyl-coA availability and glob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…This is consistent with previous studies that have demonstrated an important role for spermine, a polyamine, in controlling trophoblast metabolism and demonstrated opposite associations between maternal circulating levels of a spermine metabolite and the risk of preeclampsia and FGR. 26 , 27 As both preeclampsia and FGR are major determinants of the global burden of disease, 28 , 29 mechanistic studies are required to better understand the commonalities and differences in the pathways leading to these two placentally related complications.…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with previous studies that have demonstrated an important role for spermine, a polyamine, in controlling trophoblast metabolism and demonstrated opposite associations between maternal circulating levels of a spermine metabolite and the risk of preeclampsia and FGR. 26 , 27 As both preeclampsia and FGR are major determinants of the global burden of disease, 28 , 29 mechanistic studies are required to better understand the commonalities and differences in the pathways leading to these two placentally related complications.…”
Section: Discussionmentioning
confidence: 99%
“…One spermine metabolite, diacetylspermine, detected in maternal serum was further associated with an increased risk of PE and a reduced risk of FGR (57). Functional assays of trophoblasts revealed that placentas of male fetuses were more susceptible to polyamine depletion, which was associated with impaired mitochondrial energy metabolism, and decreased histone acetylation and progesterone synthesis (6). Moreover, genes that escape from XCI may be essential for placental function, since monosomy X has been recently shown to impair development and maturation of the STB and EVT and reduce placental hormone production in a trophoblast model derived from human-induced pluripotent stem cells carrying a single copy of the X chromosome (2).…”
Section: Placental Function In Health and Disease Fetal Sex As A Modu...mentioning
confidence: 99%
“…Moreover, genes that escape from XCI may be essential for placental function, since monosomy X has been recently shown to impair development and maturation of the STB and EVT and reduce placental hormone production in a trophoblast model derived from human-induced pluripotent stem cells carrying a single copy of the X chromosome (2). Interestingly, variable expression of the paternal allele, maternal allele, or both alleles of an X-linked gene was noted across different locations in term placentas (98) and among single nuclei of isolated trophoblasts (6). How mosaic expression of X-linked genes affects trophoblast phenotypes and contributes to sexual dimorphism in placental function and pregnancy complications are questions that merit further study.…”
Section: Placental Function In Health and Disease Fetal Sex As A Modu...mentioning
confidence: 99%
“…[322]. Additionally, depletion of polyamines in cells leads to glycolysis inhibition, suppression of the TCA cycle and OXPHOS, decreased levels of acetyl-CoA and histone acetylation, downregulation of mitochondrial metabolism genes, downregulation of TCA intermediates and OXPHOS activity, upregulation of stress signaling, and enhanced mitochondrial permeability [323,324]. For oocytes, the level of putrescine decreases with age and is one of the main factors for poor quality in the oocytes of aged mouse [325].…”
Section: Antioxidantmentioning
confidence: 99%